Risk perception towards international travellers’ destination choice: A case of Sabah / Izyan Dahlia Supani and Zuliah Abd Hamid. - Supani, Izyan Dahlia; Abd Hamid, Zuliah (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2020)
Risk and tourism are basically related to each other as it involves travelling to unfamiliar destinations; the uncertainty of future conditions; and the possible negative results of making the decision to travel. This study is designed to investigate risk factors on international traveler’s destination choice and to examine the relationship between the risk factors towards international traveler’s destination choice. The study involved a convenience sampling of 410 international travellers who were travelling to Malaysia. A quantitative approach was applied to measure the respondents’ perception of the risk factors including political instability, terrorism risk, physical risk as well as social risk towards the destination choice which is Sabah, Malaysia. The findings revealed that risk perception factors of international travellers have positively influenced the decision-making in choosing Sabah as their destination. Political instability risk attributes have the most influence on the international travellers’ choice of Sabah as compared to terrorism risk, physical risk and social risk. International travellers remain optimistic about the safety and security in Sabah, and prefer to choose Sabah as a holiday destination. Implications for future research and marketing are discussed.